TopoStats – A program for automated tracing of biomolecules from AFM images - Beton, Joseph G.; Moorehead, Robert; Helfmann, Luzie; Gray, Robert; Hoogenboom, Bart W.; Joseph, Agnel Praveen; Topf, Maya; Pyne, Alice L.B. (Methods (San Diego, Calif.), 2021)
•TopoStats is a Python toolkit for automated AFM data processing.•TopoStats takes raw data as input, and outputs processed data and statistical information without user input.•TopoStats can accurately trace linear and circular biomolecules and provide conformational analysis.•We applied TopoStats to analyse DNA minicircles, origami and pore-forming proteins.•TopoStats can be used on both ideal and contaminated samples. We present TopoStats, a Python toolkit for automated editing and analysis of Atomic Force Microscopy images. The program automates identification and tracing of individual molecules in circular and linear conformations without user input. TopoStats was able to identify and trace a range of molecules within AFM images, finding, on average, ~90% of all individual molecules and molecular assemblies within a wide field of view, and without the need for prior processing. DNA minicircles of varying size, DNA origami rings and pore forming proteins were identified and accurately traced with contour lengths of traces typically within 10 nm of the predicted contour length. TopoStats was also able to reliably identify and trace linear and enclosed circular molecules within a mixed population. The program is freely available via GitHub (https://github.com/afm-spm/TopoStats) and is intended to be modified and adapted for use if required.